Association between maternal iron supplementation and newborn birth weight: a quantile regression analysis - Guoshuai Shi; Zhuo Zhang; Lu Ma; Binyan Zhang; Shaonong Dang; Hong Yan (BMC, 2021)
Abstract Objective Our study aimed to explore the association between maternal iron supplementation and newborn birth weight (BW) in Shaanxi Province using quantile regression (QR). Method The data used in this study were derived from a large cross-sectional survey of a population in Shaanxi Province, Northwest China. A total of 28,209 women and their infants were selected using a stratified multistage random sampling method. The effect of iron supplementation on the newborn BW was assessed by a multiple linear regression model and QR. Results A total of 5.15% of the women took iron supplements during pregnancy. Multiple linear regression showed that the iron supplementation during pregnancy had positive effects on the BW, with an average increase of 43.07 g (β = 43.07, t = 3.55, and p < 0.001). The QR showed that the iron supplementation during pregnancy was associated with an increased newborn BW from very low to higher percentiles (quantiles: 0 ~ 0.40), with the β ranging from 136.51 to 43.86. As the percentiles of the BW increased, the neonatal BW gain gradually declined in the iron supplementation group compared with the group that did not receive iron supplementation (quantiles: 0 ~ 0.40, with the β ranging from 136.51 to 43.86). Iron supplementation was more effective among women who suffered from anemia during pregnancy (β = 45.84, t = 2.05, and p = 0.04; quantiles: 0 ~ 0.15, 0.30, 0.80, with β ranging from 150.00 to 39.29) than it was in any other group (β = 38.18, t = 2.62, and p = 0.009; quantiles: 0 ~ 0.15, with β ranging from 133.33 to 28.32). Conclusions Iron supplementation during pregnancy is associated with an increased newborn BW, and the effect was more obvious in the newborns with the lower BW and newborns whose mothers suffered from anemia during pregnancy.